Preimplantation genetic testing: method and two case studies of familial three-way complex translocations. Issue 1 (1st January 2019) - Staykova, Slavyana Yaneva; Staneva, Rada; Stamenov, Georgi; Pancheva, Maria; Serafimova, Maria; Nikolova, Kristina; Toncheva, Draga; Hadjidekova, Savina
Abstract: Preimplantation genetic testing (PGT) is presently the only option available for detecting genetic conditions in embryos created through in vitro fertilization (IVF) prior to implantation. Thus PGT eliminates the dilemma of pregnancy termination following unfavorable prenatal diagnosis test results. Complex chromosome rearrangements (CCRs), although very rarely reported in humans, represent a significant clinical problem for their carriers. CCRs include at least three breakpoints affecting two or more chromosomes. In three-breakpoint translocations, theoretically sixty-four different chromosomal sets are produced. Only two of them will be balanced and will lead to the birth of a phenotypically normal child. Therefore, CCR carriers are at increased risk of chromosomally unbalanced conceptions, resulting in spontaneous abortions or birth of offspring with intellectual disability and/or congenital anomalies. The reproductive options before such families are: natural conception followed by prenatal diagnosis; donor gametes; adoption or PGT. In this paper we discuss the current state of the PGT field and report on two PGT-cases for CCR in families with infertility and recurrent pregnancy losses. The families underwent IVF-PGT on day 3 and day 5 embryos and whole genome microarray analysis.